2015
DOI: 10.1016/j.jdiacomp.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Non-transferrin-bound iron is associated with biomarkers of oxidative stress, inflammation and endothelial dysfunction in type 2 diabetes

Abstract: These results support the hypothesis that iron-mediated oxidative stress may be a mechanism linking poor glycaemic control with vascular dysfunction in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…A subsequent one-electron reduction of ferric to ferrous iron and also producing dehydroascorbate (DHA) can be obtained by oxidation of AFR [4,23]. An alternative mechanism may involve electron transference by tunnelling through the protein via an electron transport chain.…”
Section: Release Of Iron From Ferritinmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent one-electron reduction of ferric to ferrous iron and also producing dehydroascorbate (DHA) can be obtained by oxidation of AFR [4,23]. An alternative mechanism may involve electron transference by tunnelling through the protein via an electron transport chain.…”
Section: Release Of Iron From Ferritinmentioning
confidence: 99%
“…Free "labile" iron activity within body fluids is normally very low and present mainly as hydrated complexes in proteins, such as albumin, or as low molecular weight chelates with citrate or glutathione [2]. In the plasma of patients suffering from iron overload, the amount of redox active and chelatable nontransferrin bound iron (NTBI) is in the range of 1-20 µM [3][4][5]. Ascorbic acid is highly concentrated in a few tissues, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous forms of body iron exist, and only forms not bound to transferrin or other iron-binding proteins named non-transferrin-bound iron (NTBI) seem to be implicated in oxidative damages due to their high reactivity [248]. NBTI could be considered a biomarker of the side effect of iron in diseases, greatly correlated with Hb1Ac [249]. Recently, Aljwaid et al [249] confirmed association of NTBI with the risk of vascular complications in diabetes already highlighted 10 years earlier [250,251,252], because NBTI is easily accessible to plaque as well as endothelial cells, macrophages, and smooth muscle cells.…”
Section: Oxidative Stress and Cardiovascular Complicationsmentioning
confidence: 99%
“…NBTI could be considered a biomarker of the side effect of iron in diseases, greatly correlated with Hb1Ac [249]. Recently, Aljwaid et al [249] confirmed association of NTBI with the risk of vascular complications in diabetes already highlighted 10 years earlier [250,251,252], because NBTI is easily accessible to plaque as well as endothelial cells, macrophages, and smooth muscle cells. Inflammation contributes to iron-mediated endothelial dysfunction, characterized by a high release of iron by infiltrated macrophages, an increase in E-selectin, and other adhesion molecules implicated in atherosclerotic plaque [247,253].…”
Section: Oxidative Stress and Cardiovascular Complicationsmentioning
confidence: 99%
“…Measures of hepcidin, NTBI [74][75][76], glycated hemoglobin, insulin resistance, inflammation and possibly other variables were not available in this study. T2D risk may also be attributable to socio-economic factors, environmental contaminants [77][78][79] or Western Lifestyles [80]. These require further investigation of their effects on iron biomarkers and associated iron metabolism.…”
Section: Limitations Of This Studymentioning
confidence: 99%